2020
DOI: 10.1002/app.49747
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of PLA thermal behavior during fused filament fabrication

Abstract: Fused filament fabrication (FFF) is an additive manufacturing technique that is used to produce prototypes and a gradually more important processing route to obtain final products. Due to the layer-by-layer deposition mechanism involved, bonding between adjacent layers is controlled by the thermal energy of the material being printed, which strongly depends on the temperature development of the filaments during the deposition sequence. This study reports experimental measurements of filament temperature during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…The mechanical behavior of PLA specimens using FDM under both static and fatigue loadings is influenced mainly by the following parameters: filling temperature, filling rate, filling pattern, layer thickness, infill percentage, nozzle size and manufacturing orientation. According to the previous works (Vanaei et al , 2020d), the temperature of extruder is the main parameter which influences the mechanical properties of PLA sample manufactured using FDM process.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical behavior of PLA specimens using FDM under both static and fatigue loadings is influenced mainly by the following parameters: filling temperature, filling rate, filling pattern, layer thickness, infill percentage, nozzle size and manufacturing orientation. According to the previous works (Vanaei et al , 2020d), the temperature of extruder is the main parameter which influences the mechanical properties of PLA sample manufactured using FDM process.…”
Section: Discussionmentioning
confidence: 99%
“…To track filaments cooling and the re-heating peaks of deposition of successive layers, a very small (d = 80 lm) K-type thermocouple was used (see [28,29] for method description). Results and discussion…”
Section: Online Temperature Measurement Of Filamentsmentioning
confidence: 99%
“…To track the cooling of filaments and the re‐heating peaks of deposition of successive layers during deposition, very small (d = 80 μm) K‐type thermocouples were used (see [ 23 ] for method description). The schematic of the experiment is presented in Figure 1 containing: the set‐up for in‐process measurement of temperature profile during the deposition, assembling of two methods together, and thermogram of the printed vertical wall with corresponding layers and locations highlighted for temperature profile.…”
Section: Methodsmentioning
confidence: 99%
“…To address this limitation, K‐type thermocouples (d = 80 μm) were added in parallel with deposition without pausing the process or causing damage. [ 23 ] The experimental data were then compared with the predictions obtained by Costa et al [ 24 ] and it was found that there is a sufficient agreement between the experimental and analytical results.…”
Section: Introductionmentioning
confidence: 97%